A CROSS-SECTIONAL ASSESSMENT OF PHARMACISTS’ KNOWLEDGE, ATTITUDE AND PRACTICE OF PREVENTION OF MOTHER-TO-CHILD TRANSMISSION OF HIV IN TWO NIGERIAN TEACHING HOSPITALS: Pharmacists’ Knowledge, Attitude and Practice of PMTCT - ISAH, Abdulmuminu; ABUBAKAR, Mustapha Muhammed; IGBOELI, Nneka Uchenna; IBEZIM, Isaac Chijioke; IBENEKWU, Chisom Sandra (African Journal of Infectious Diseases (AJID), 2022)
Background: The pharmacological component of prevention of mother-to-child transmission (PMTCT) services involves the provision of antiretroviral agents (ARVs) to the mothers and/or their babies at any stage of pregnancy. This study assessed the knowledge, attitude and practice (KAP) of Pharmacists about PMTCT. Materials and Methods: A questionnaire-based cross-sectional study was conducted among consenting Pharmacists at Ahmadu Bello University Teaching Hospital (ABUTH) and University of Nigeria Teaching Hospital (UNTH). Completed questionnaires were collated and analyzed using SPSS Version-25 with appropriate descriptive and inferential statistics. P-values less than 0.05 were considered to be statistically significant. Results: A total of 77 Pharmacists participated in the study, with 54(70.13%) being from ABUTH. In ABUTH, 15(33.3%) Pharmacists identified as being females, against 16(69.6%) in UNTH. Majority (40,95.2%) of the Pharmacists in ABUTH had less than 10 years working experience as against 8(34.8%) in UNTH. Forty-eight (88.9%) respondents knew the correct meaning of PMTCT. The Pharmacists in ABUTH and UNTH had mean knowledge scores of 58.70±2.88% and 52.17±6.19%, respectively; t(75)=1.094, p=0.760. In ABUTH and UNTH, 16(69.6%) and 22(42.3%) Pharmacists, respectively, strongly agreed that PMTCT can prevent future infections in the infants. Their mean attitude scores were 69.65±1.22% (ABUTH) and 74.09±1.68% (UNTH); t(73)=-2.063, p=0.487. For practice, 4(5.33%) Pharmacists in both hospitals very often dispensed PMTCT drugs, while 37(70.83%) counseled PMTCT treatment-naïve patients. Conclusion: The Pharmacists assessed in both hospitals had a fair knowledge of PMTCT services. Their attitudes to PMTCT was very good, although only a few of them had experience in providing care for PMTCT patients.